The Development of E-Worksheet Based on Sets (Science, Environment, Technology, Society) for Waste Processing Sub-Topic to Improve Student's Scientific Literacy Skills - Muhammad Yusuf Abdul Rochim; Fida Rachmadiarti; Dwi Anggorowati Rahayu (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2022)
The development of the 21st century learning demands scientific literacy competence. One of the things that can be used to train scientific literacy is with learning materials that integrate Science, Environment, Technology, Society (SETS). SETS-based learning is learning model that connects and links the science concepts studied with other fields, namely technology, environment and society. The aims of this study was to develop E-LKPD based on SETS for waste processing sub-materials to improve students scientific literacy which is theoretically and empirically feasible for learning process. The theoretical feasibility of E-LKPD is reviewed from the validation results assessed by material expert lecturers, education expert lecturers and biology teachers. The empirical feasibility can be seen from students response. This research is a development research using the 4D method (define, design, develop, disseminate) without doing the disseminate stage. The data analysis technique used quantitative description method. The results showed that the E-LKPD is declared theoretically feasible with a validation percentage of 97% with a very valid category. E-LKPD was also declared empirically feasible by getting a positive response from students with a practicality percentage of 97% with a very practical category. Hence, it can be concluded that the E-LKPD based on SETS for waste processing topic to improve students' scientific literacy is declared theoretically and empirically feasible for learning process. The implication of this research is to help improve the scientific literacy of Indonesian students, which is still considered low. Through the development of this E-LKPD is one of the efforts to improve Indonesian students in scientific literacy. Keywords: E-worksheet, SETS, Scientific Literacy